Cratoxylum glaucum and cratoxylum arborescens (Guttiferae)-two potential source of antioxidant agents. - Ee, Gwendoline Cheng Lian; Md.Sukari, Mohd. Aspollah; Sim, W.C.; Lim, C.J. (Chemical Publishing Co., 2011)
Our detailed chemical studies on Cratoxylum glaucum and C. arborescens have revealed the presence of 5-demethoxycadensin G (1), fuscaxanthone C (2), b-mangostin (3), 3-geranyloxy-6-methyl-1,8-dihydroxyanthraquinone (4), vismiaquinone (5), 1,8-dihydroxy-3-methoxy-6-methylanthraquinone (6), stigmasterol (7) and friedelin (8). Structural elucidations of these compounds were achieved by using 1D and 2D NMR spectroscopic experiments. Antioxidant tests conducted on these two plant species gave promising results with both species indicating good antioxidant inhibiting properties. This is a first report on 5-demethoxycadensin G (1) and b-mangostin (3) from Cratoxylum glaucum as well as the antioxidant properties of these two species.